The Risk of Large Hernias in Patients with Abdominal Defects Starting Hemodialysis - Nasir Naseem Akhtar, Shahzad Shokat, Zareena Jan, Shafat, Jawad Ahmed (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The initiation of hemodialysis in patients with pre-existing abdominal defects presents a unique set of challenges, including the heightened risk of developing large hernias. Objective: This study aimed to investigate the incidence of large hernias and the associated risk factors in patients beginning hemodialysis. Methods: This retrospective study was conducted at department of General Surgery Mayo Hospital Lahore during august 2022 to may 2023. A total of 105 patients were added in the study. Data were collected through a comprehensive review of patient medical records, including demographic details (age, sex, and comorbid conditions), clinical history (previous abdominal surgeries, hernias, and comorbidities like diabetes and obesity), and dialysis-related information (type of dialysis access, complications during dialysis initiation, and duration of dialysis). Results: Twenty-two patients (21%) developed large hernias within six months of initiating hemodialysis. Risk factors for hernia development included prior abdominal surgery (p < 0.01) and obesity (p = 0.04). The majority of hernias were managed surgically (68%), with the rest managed conservatively. The most common locations of hernias were the umbilical (45%) and inguinal (35%) regions. Hernia-related complications, such as bowel obstruction, were observed in 27% of patients with large hernias. Dialysis access complications, including difficulties with catheter placement and migration, were noted in 23% of patients with hernias. Conclusion: It is concluded that patients with abdominal defects, particularly those with a history of abdominal surgery or obesity, are at a significantly increased risk of developing large hernias when starting hemodialysis. Keywords: Large Hernia, Abnormal Defects, Hemodialysis